Implementasi Kurikulum Merdeka melalui Projek Penguatan Profil Pelajar Pancasila (P5) - Putri, Novela Aurora; Hardi, Sean Popo; Tabroni (IBTIDA', 2024)
This article discusses the implementation of the Merdeka curriculum through a project to strengthen the profile of Pancasila students. The project to strengthen the profile of Pancasila students is one of the new programs designed by the Ministry of Education and Culture in the Merdeka curriculum. The aims of this research are: (1) to describe the planning of the project to strengthen the profile of Pancasila students in 58 state elementary schools in Jambi City, (2) to describe the implementation of the project to strengthen the profile of Pancasila students in 58 state elementary schools in Jambi City, (3) to describe what just the obstacles in implementing the project to strengthen the profile of Pancasila students in 58 state elementary schools in Jambi City. This research is qualitative research with a descriptive type. This research was conducted at State Elementary School 58, Jambi City, class IV. The data sources in this research were the principal of State Elementary School 58, Jambi City and the class IV teacher of State Elementary School 58, Jambi City. Data collection techniques used interviews, observation and documentation. The data analysis technique in this research uses the interactive method of Miles, Huberman and Saldana with the steps: 1) data condensation, 2) data presentation, 3) drawing conclusions. The data validity method uses source triangulation and technical triangulation. The results of the research show that: 1) The planning stage is forming a P5 facilitator team, identifying school readiness, determining themes that will be used in the project to strengthen the Pancasila student profile, determining time allocation, and preparing teaching modules that will be used. 2) At the P5 implementation stage, namely carrying out preparation of learning resources, project work, evaluation stages. The inhibiting factor in implementing P5 is that the timing of its implementation is still not conducive because implementing P5 requires a long time, and the school land is not sufficient.